PHILOSOPHICAL ANALYSIS OF DAN BROWN'S GENESIS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article discusses the development and achievements of science on the basis of the realities expressed in Genesis, as well as the philosophical analysis of the phenomena observed in society as a result of the mental development of mankind